Evaluation of replicas manufactured in a 3D-printed nanoimprint unit - Caño-García, Manuel; Geday, Morten A.; Gil-Valverde, Manuel; Quintana, Xabier; Otón, José Manuel (Beilstein Journal of Nanotechnology, 2018)
Nanoimprint lithography has become a useful tool to prepare elements containing nanoscale features at quite reasonable cost, especially if the fabrication elements are created in the own laboratory. We have designed and fabricated a whole nanoimprint manufacturing system and analyzed the resulting surfaces using ad hoc packages developed on an open-software AFM image analysis suite. To complete the work, a number of polymers have been thoroughly studied in order to select the best material for this implementation. It turned out that the best alternative was not always the same, but depended on the application. A comparative study of the polymers, which takes into account the values and dispersion of numerous sample parameters, has been carried out. As a large number of samples was prepared, an automatized procedure for characterization of nanoimprint surfaces had to be set up. The procedure includes figures of merit for comparative purposes. Materials without the requirement of a solvent were found to be superior for most nanoimprint applications. A large dispersion of the samples was found.
Keywords: nanoimprint; oriented gradient; photoresist; polymer; replica